Nanomaterials for biosensors - Kumar, C. S. S. R. (Challa S. S. R.) (Nanotechnologies for the life sciences, 2006)
Volume 8 covers a wide range of materials and design conceps for biosensors. Different kinds of nanoscale particles, rods, wires and structures offer numerous opportunities for biological material detection and analysis, and materials as well as applications and instrumentational issues are addressed in detail.